2022
DOI: 10.1039/d1fd00118c
|View full text |Cite
|
Sign up to set email alerts
|

Gently does it!: in situ preparation of alkali metal–solid electrolyte interfaces for photoelectron spectroscopy

Abstract: The key charge transfer processes in energy storage devices occur at the electrode-electrolyte interface, which is typically buried making it challenging to access the interfacial chemistry. In the case of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…A very similar evolution of the P 2p spectra was observed during in situ XPS of LiPON 55 Finally, a new feature at lower BE was detected in the O 1s spectra, which grew to dominate with time and could be assigned to Li2O. Although there will be some Li2O present due to the deposited Li reacting with surface contaminants and trace O2/H2O present inside the XPS chamber, 56 it is likely that a majority of the Li2O formed as a result of direct reaction with LAPO considering the greater impedance of the interphase. Therefore, the passivation layer was found to be a mixture of Li2O, Li3P, LixP and Al 0 species.…”
Section: In Situ Xps During LI Depositionsupporting
confidence: 67%
“…A very similar evolution of the P 2p spectra was observed during in situ XPS of LiPON 55 Finally, a new feature at lower BE was detected in the O 1s spectra, which grew to dominate with time and could be assigned to Li2O. Although there will be some Li2O present due to the deposited Li reacting with surface contaminants and trace O2/H2O present inside the XPS chamber, 56 it is likely that a majority of the Li2O formed as a result of direct reaction with LAPO considering the greater impedance of the interphase. Therefore, the passivation layer was found to be a mixture of Li2O, Li3P, LixP and Al 0 species.…”
Section: In Situ Xps During LI Depositionsupporting
confidence: 67%
“…During the lithium diffusivity experiments, care was taken to minimize the presence of contamination at the interface between the evaporated tracer thin films and the 6 Li or 7 Li-Mg substrates. Lithium and Li-Mg alloy samples will rapidly react with trace moisture, oxygen, carbon dioxide, and nitrogen in a glovebox and even in the vacuum in the thermal evaporation chamber. , Mindful of this, exposure of the fresh lithium and Li-Mg alloy surfaces to the glovebox atmosphere was kept to a minimum (<1 min) before evacuation of the thermal evaporation chamber. However, the presence of some contamination is unavoidable, and in order to understand its effect on the lithium diffusivity, Figure a compares two diffusion profiles of 7 Li into 6 Li where the 6 Li substrate was prepared in glovebox atmospheres with different contamination levels prior to the 7 Li tracer deposition.…”
mentioning
confidence: 99%
“…12 We note that recent studies suggested that dual mode charge compensating XPS instruments (such as the one employed in this study) may alter the chemistry of the interphase because of the energy provided by the impacts from Ar + ions on the surface. 15 To minimize this effect, the Ar + ion current was reduced in this study.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication demonstrated that the bombardment of the interface by Ar + ions during plating can impact the interphase composition. 15 To minimize the Ar + ion flux reaching the interface, the extractor voltage of the instrument was reduced to 30 V following the results of a previous study. 16 The Na 0 plating rate was controlled by optimizing the FG parameters: the beam voltage was set to 3 V, and the current was set to 30 μA (the actual electronic current reaching the sample surface was measured using a Faraday cup and a value of ~4.8 μA was found; the Ar + current reaching the surface is ~10 nA).The base pressure of the instrument (FG off) is typically around 1 x 10 -9 mbar and rises to around 1 x 10 -8 mbar when the FG is activated.…”
Section: X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%